Particulate Matter Induces NLRP3 Inflammasome-Mediated Pyroptosis in Human Nasal Epithelial Cells - Hosung Choi; Hyunsu Choi; Jeong-Min Oh; Dong Chang Lee (Journal of Rhinology)
Background and Objectives Air pollution, particularly particulate matter (PM), has a variety of adverse effects on human health. PM is known to induce cell death through various pathways, including pyroptosis. Despite its significance, research on PM-induced pyroptosis in nasal epithelial cells remains limited. This study aimed to explore PM-induced pyroptosis in cultured human nasal epithelial cells. Methods For the in vitro experiments, human nasal epithelial cells were cultured. Cell viability was assessed using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, while cell death was evaluated through propidium iodide (PI) staining and lactate dehydrogenase (LDH) release measurement. Protein expression levels related to pyroptosis were examined via western blot using antibodies against NOD-like receptor family, pyrin domain containing 3 (NLRP3), cleaved caspase-1 (CASP1 P20), gasdermin D (GSDMD)-N, and glyceraldehyde phosphate dehydrogenase. Immunofluorescent staining with a CASP1 P20 antibody was conducted to visualize cellular localization. Enzyme-linked immunosorbent assay was utilized to quantify interleukin (IL)-1β and IL-18 protein levels. Results Treatment with PM resulted in decreased cell viability, elevated LDH release, and intensified PI staining, indicating cell death. Pyroptosis was confirmed by the elevated expression of NLRP3, CASP1 P20, and GSDMD-N, along with increased levels of IL-1β and IL-18. Inhibiting the NLRP3 inflammasome with MCC950 reduced the PM-induced effects on protein expression and cytokine release, highlighting the role of the NLRP3 inflammasome in PM-triggered pyroptosis in human nasal epithelial cells. Conclusion We showed that PM triggers pyroptosis in human nasal epithelial cells, driven by NLRP3 inflammasome-dependent signaling pathways.